Unraveling chronic kidney disease in children: a surprising manifestation of celiac disease - Starcea, Iuliana Magdalena; Miron, Ingrith; Lupu, Ancuta; Ioniuc, Ileana; Alecsa, Mirabela; Azoicai, Alice; Morariu, Ionela Daniela; Munteanu, Valentin; Lupu, Vasile Valeriu; Mocanu, Adriana (Frontiers in Pediatrics, 2024)
Celiac disease, firstly described in children, is a type of T-cell enteropathy that occurs in individuals genetically predisposed to gluten exposure. The estimated global prevalence of celiac disease is continuously increasing. Although, traditionally, celiac disease was diagnosed in children with failure to thrive and digestive issues, it is now recognized that may present with a wide range of symptoms beyond gastrointestinal ones. Celiac disease continues to pose significant challenges due to the continuous advancement of knowledge in understanding its pathophysiology, diagnosing the condition, managing its effects, and exploring potential therapeutic approaches. The prevalence of celiac disease is increased among individuals with chronic kidney disease, also. The most frequent associations are with diabetic nephropathy, IgA nephropathy and urolithiasis. A gut-kidney axis has been recognized to play a significant role in chronic kidney diseases. This literature review aims to review the chronic renal pathology associated with celiac disease, with emphasis on childhood.